Pharmacological blockade of dopamine D1- or D2-receptor in the prefrontal cortex induces attentional impairment in the object-based attention test through different neuronal circuits in mice - Wulaer, Bolati (Mol Brain, 2021)
Dopamine is a key neurotransmitter that regulates attention through dopamine D1 and D2-receptors in the prefrontal cortex (PFC). We previously developed an object-based attention test (OBAT) to evaluate attention in mice. Disruption of the dopaminergic neuronal system in the PFC induced attentional impairment in the OBAT. However, previous studies have not systematically examined which specific brain regions are associated with the blockade of PFC dopamine D1 and D2-receptors in the OBAT. In this study, we investigated the association of dopamine D1 and D2-receptors in the PFC with attention and neuronal activity in diverse brain regions. We found that both dopamine D1 and D2-receptor antagonists induced attentional impairment in the OBAT by bilateral microinjection into the PFC of mice, suggesting that both dopamine D1 and D2-receptors were associated with attention in the OBAT. Our analysis of the neuronal activity as indicated by c-Fos expression in 11 different brain regions showed that based on the antagonist types, there was selective activation of several brain regions. Overall, this study suggests that both dopamine D1 and D2-receptors play a role in attention through different neuronal circuits in the PFC of mice.